Prevalence of diabetic retinopathy in patients in a tertiary hospital in south India - Jayalekshmi T; K P Poulose (International Journal of Medical Research and Review, 2016)
Aims: To estimate the prevalence of Retinopathy in patients attending a diabetic clinic and to evaluate the risk factors underlying its development.Methods: 750 diabetic patients who reported for executive check up in a preventive clinic were evaluated for absence or presence of retinopathy. Diabetic Retinopathy (DR) present was graded as non proliferative diabetic retinopathy (NPDR) and proliferative diabetic retinopathy (PDR). Risk factors were then evaluated in order to delineate those related to retinopathy. Investigations included complete blood count, blood sugar, serum lipids, ECG, Renal function tests and complete clinical examination.Results: DR was detected in 111 patients (14.8 %) with NPDR in 106 patients (14.1%) and PDR in 5 patients (0.7%). Factors related to the incidence of retinopathy were duration of diabetes, presence of hypertension, high blood sugar level and hyperlipidemia. It was found that duration of diabetes, level of glycemic control and high levels of cholesterol were statistically significant for the occurrence of retinopathy.Conclusion: In addition to glycemic control, lowering of serum lipids may be effective in lowering the incidence of retinopathy in diabetic patients .Hypertension was not related to the occurrence of retinopathy.